Model Pola Karir Jabatan Struktural Tenaga Kependidikan di Institut Seni Budaya Indonesia Bandung - Gian Aditya Chandra; Ely Sufianti; Teni Listiani (Jurnal Media Administrasi Terapan, 2022)
This research is a Model of Educational Personnel Career Patterns at the Indonesian Art and Culture Institute Bandung. The research method used is a qualitative research method aimed at analyzing the career patterns of employees based on career management and career planning, analyzing the inhibiting factors that occur in the implementation of educational personnel career patterns and creating models that support the career pattern processes of educational personnel at ISBI Bandung so that support in the process of determining one's career position in an executive position in accordance with the competence and also support the organizational pattern. The results showed that the career pattern of employees at ISBI Bandung, both in terms of career management and career planning at ISBI Bandung, is still not optimal even though there are certain parts that have been implemented and become part of the support process for the career development of employees at ISBI Bandung. From the results of the study, two models of career patterns are offered to help the career pattern program at ISBI Bandung by the author, namely the career pattern model based on job clumps and the zig-zag career pattern model.